The expression of emotion: philosophical, psychological and legal perspectives - Catharine Abell (ed.); Joel Smith (ed.) (U K: Cambridge, 2016)
"The Expression of Emotion collects cutting-edge essays on emotional expression written by leading philosophers, psychologists, and legal theorists. It highlights areas of interdisciplinary research interest, including facial expression, expressive action, and the role of both normativity and context in emotion perception. Whilst philosophical discussion of emotional expression has addressed the nature of expression and its relation to action theory, psychological work on the topic has focused on the specific mechanisms underpinning different facial expressions and their recognition. Further, work in both legal and political theory has had much to say about the normative role of emotional expressions, but would benefit from greater engagement with both psychological and philosophical research. In combining philosophical, psychological, and legal work on emotional expression, the present volume brings these distinct approaches into a productive conversation"--
Keywords: Emotions Phylosophical Aspects; Emotions; Psychology